Super‐Heterostructures of Twisted Pd Nanoarrays Epitaxially Grown on Chiral Au Nanorods Boost Circularly Polarized Photocatalysis - Taotao Luo; Haoyu Li; Zhicheng Zhang; Shenli Wang; Xiaobin Pan; Stefanos Mourdikoudis; Chao Xue; Junjun Li; Kwok‐Yin Wong; Guangchao Zheng (Advanced Science, 2025)
Abstract Seed‐mediated growth provides an efficient way to produce chiral hybrid nanocrystals, mainly benefitting from the recent successful synthesis of discrete chiral metal nanocrystals. However, the chiroptical response of chiral core‐shell nanostructures decreases rapidly when the functional layer is grown on the discrete chiral metal nanocrystals. Herein, a synthetic methodology is demonstrated for the formation of chiral Au@Pd super‐heterostructures, in which Pd nanoarrays are epitaxially and densely grown with a twisted lattice on discrete chiral Au nanorods (Pd‐on‐cAuNRs). The highly aligned Pd nanoarrays on cAuNRs exhibit good chiroptical performance. Importantly, the Pd‐on‐cAuNR super‐heterostructures display chiral behavior in their catalytic actions, with the catalytic performance of D‐super‐heterostructures being twice higher than that of its L‐ super‐heterostructures. In addition, under circularly polarized light (CPL) irradiation, the chiral electromagnetic field and hot electrons generated on the chiral super‐heterostructures boost circularly polarized photocatalytic activity, the mechanism of which is supported by theoretical simulations and chiral photocurrent experiments. This research work offers fundamental insights on chiral surface plasmon resonance‐induced photocatalysis and rational design of chiral nanostructure photocatalysts.